Considerations for the use of brain endurance training in elite sport: A narrative review - Joseph, S. D.; Russell, S.; Tofari, P. J.; Halson, S. L.; Johnston, R. D.; Timmins, R. G.; Murray, N. B.; Cormack, S. J. (Scandinavian Journal of Medicine & Science in Sports, 2026)
Brain endurance training (BET) has been proposed as a method to enhance resistance to mental fatigue (MF) and mitigate the negative effects of MF on performance. The use of BET has been associated with improvements in endurance performance, cognitive function, skill performance, and reduced perception of effort under conditions of MF in amateur and professional athletes. However, the effectiveness and optimal application of BET in elite athletes (performance tier 4-5) has yet to be identified in the preliminary investigations available. This narrative review examined 12 published BET intervention studies to review BET methodology, performance impacts, and identify if BET may be beneficial to elite athlete performance. This review identified potential barriers and facilitators to the practical implementation for elite athletes. Existing research indicates that BET may be useful to maximize resistance to MF or enhance resistance to performance decrements resulting from MF in performance tier 0-3 athletes and should be examined to assess potential benefit for elite athletes. Benefits may exist in enhancing endurance performance, skill execution, and during injury rehabilitation. However, clear guidelines regarding efficacy and implementation are limited by substantial variation in research methodology and a lack of ecologically valid studies. Future research should aim to assess BET in elite athletes in an ecologically valid context to determine if it offers similar benefits shown in non-elite athletes. Furthermore, research should examine the effect of varying dosages of BET in elite athletes.